The emergence of e-cigarette retail shops in a regulated tobacco control environment - Scott, Lucy; McCausland, Kahlia; Maycock, Bruce; Jancey, Jonine (WILEY, 2022)
Issue addressed: E-cigarettes are of growing concern. We aimed to determine the location and characteristics of retail shops selling e-cigarette products in Perth, Western Australia. Methods: Two phase study: (i) identifying all e-cigarette retailers in the Greater Capital City Statistical Area of Perth; (ii) audit at the point-of-sale to assess products, promotions and shop characteristics (n = 41). Results: Ninety-eight retailers selling e-cigarette products were identified: 43 tobacconists (44%), 21 vape shops (21% – up from one shop in 2017), 14 supermarkets (14%), 12 service stations (12%) and 8 smoke shops (8%). The most common e-cigarette product was non-nicotine e-liquid, available at 38 (93%) stores audited. Most stores sold parts of e-cigarette devices (n = 25, 61%). Front counter displays were the most frequent form of promotion (n = 40, 98%). Vape shops differed from other retailers, having bar-style layouts (n = 15, 71%), lounge areas (n = 7, 33%) and free e-liquid samples (n = 17, 89%). Conclusion: The availability of e-cigarette products from retail shops and particularly vape shops is increasing. E-cigarette retailers are using traditional promotional techniques including point-of-sale displays to market their products, while vape shops are extending their appeal through bar style, lounge layouts and free trials. Implications for public health: Understanding the e-cigarette retail store environment is essential for identifying emergent trends, potential regulations and future research. So what?: The e-cigarette retail market in the Perth is growing, shops using traditional and new promotional techniques to market e-cigarette products. Our findings identify a need for public health surveillance, regulations and legislation.